PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS WEBSITE LIVEWORKSHEET PADA MATERI PPKN KELAS V SD NEGERI 3 GETAS TEMANGGUNG - Novitasari, Novitasari; Wibawa , Sutrisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
21st century education has demands that students are expected to be able to master the 4C skills (critical thinking, collaborative, creativity, communication) as learning indicators which can be achieved through the development of live worksheet-based electronic student worksheets (e-LKPD) which contain indicators of critical thinking skills to train students' critical thinking skills. This research was motivated by the lack of availability of teaching materials used during learning. Teachers are still lacking in using interactive media such as electronic LKPD media. This research aims to produce a product in the form of e-LKPD based on Liveworksheets on human movement organs for class V elementary school. Research and Development (R&D) research with the ADDIE development model is the type of research used in developing this LKPD. The research was carried out at SDN 3 Getas Temanggung in the even semester of the 2023/2024 academic year. The results of this research show that LKPD based on live worksheet software is feasible with an achievement percentage of 75% according to media experts, and 91.75% according to material experts. The results of trials on students showed a percentage of 73.52% with good criteria. The conclusion from research on LKPD based on live worksheet software on PPKn material on the rights and obligations of citizens is that it is feasible and interesting to use as a learning evaluation medium for class V students.